State defense strategy through defense public policy analysis in the face of revolution in military affairs - Lukman Yudho Prakoso (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
State defense is a very important field to be realized to be strong, but there are many obstacles to achieving the desired defense goals. Based on the various obstacles, the priority is the provision of quality human resources. Public policy in the field of government regarding the management of civil and military human resources is equally important in realizing human resources that can produce defense technology that has a deterrent effect. This study aims to analyze the national defense system through the analysis of public defense policies in the face of a Revolution in the Military Affairs (RMA). The research method used is a qualitative approach. Data was collected through Focus Group Discussion (FGD), in-depth interviews and literature review. The characteristics of the informants in this study were 12 students of the year 2020 Marine Defense Strategy study program who had taken state defense strategy courses at the Defense University. The student is a member of the Indonesian Navy (TNI). The results of this study indicate that to realize reliable human resources without losing their identity requires an understanding of defense public policy. Changes in defense technology are also related to the RMA which continues to move forward and affects the interaction of international relations. In addition, in the face of change, the role of education is needed as a tool to keep up with actual and factual changes